2018
DOI: 10.1111/epi.14447
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital population pharmacokinetics across the pediatric age spectrum

Abstract: Phenobarbital dosing of 30 mg kg dose ,iv, followed by 4 mg kg d had the highest probability of attaining a therapeutic concentration at 7 days. Postmenstrual age and drug-drug interactions should be incorporated into dosing decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 29 publications
2
50
1
Order By: Relevance
“…To the Editors: We have read with great interest the article "Phenobarbital population pharmacokinetics across the pediatric age spectrum" by Moffett et al 1 The authors concluded that midazolam, phenytoin, and pantoprazole significantly affected phenobarbital clearance and that these drug-drug interactions should be incorporated into dosing decisions. We are of the opinion that such a conclusion and dosing adjustment recommendation are not supported by scientifically sound evidence in its totality.…”
Section: Impact Of Drug-drug Interactions On Phenobarbital Pharmacokimentioning
confidence: 99%
“…To the Editors: We have read with great interest the article "Phenobarbital population pharmacokinetics across the pediatric age spectrum" by Moffett et al 1 The authors concluded that midazolam, phenytoin, and pantoprazole significantly affected phenobarbital clearance and that these drug-drug interactions should be incorporated into dosing decisions. We are of the opinion that such a conclusion and dosing adjustment recommendation are not supported by scientifically sound evidence in its totality.…”
Section: Impact Of Drug-drug Interactions On Phenobarbital Pharmacokimentioning
confidence: 99%
“…It is metabolized by the liver via cytochrome P450 and primarily excreted by the kidneys 12 . PHB pharmacokinetics is notable for maturation‐related changes in clearance in the first months of life, auto‐inducible clearance with use, and numerous drug interactions 12,13 . Prior studies in neonates, including randomized controlled trials, have reported PHB efficacy of 40%‐50% for neonatal seizures, although success rates as high as 72% have been reported 14–17 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the drug–drug interactions of midazolam, phenytoin, and pantoprazole significantly affected phenobarbital concentrations. [1]…”
mentioning
confidence: 99%
“…The bioavailability of Phenobarbital has been documented at ~90% in adults and shown to be much less in neonatal populations [1]. It is hypothesized that growth-related changes in organ function and maturation of enzyme systems used to metabolize phenobarbital (2C19 subunit of the CYP Enzyme, matures significantly in first 6 months of life) play a factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation